What is the elephant in the room when considering new therapies for fungal diseases?. (4th May 2021) - Chaves, Alison Felipe Alencar; Xander, Patricia; Romera, Lavínia Maria Dal'Mas; Fonseca, Fernando Luiz Affonso; Batista, Wagner Luiz
Abstract: The global scenario of antimicrobial resistance is alarming, and the development of new drugs has not appeared to make substantial progress. The constraints on drug discovery are due to difficulties in finding new targets for therapy, the high cost of development, and the mismatch between the time of drug introduction in a clinic and microorganism adaptation to a drug. Policies to address neglected diseases miss the broad spectrum of mycosis. Society is not aware of the actual threat represented by fungi to human health, food security, and biodiversity. The evidence discussed here is critical for warning governments to establish effective surveillance policies for fungi. HIGHLIGHTS: Fungal diseases are ignored even among neglected disease classifications. There are few options to treat mycoses, which is an increasing concern regarding fungal resistance to drugs, as evidenced by the spread of Candida auris . Fungal diseases represent a real threat to human health and food security. Investment in research to investigate the potential of repurposing drugs already in use could obtain results in the short term.